(untitled) (Al-Academy, 2025)
Research Abstract: The present study aims to identify the nature of augmented reality technology as it relates to contemporary artworks, It also seeks to uncover the aesthetic values embedded within augmented reality technology, The researcher employed the descriptive-analytical method to analyze contemporary artworks that utilize augmented reality, The research population comprised all contemporary artworks based on augmented reality technology, while the sample consisted of an analysis of five (5) contemporary artworks in the field of visual arts based on augmented reality technology, and among the key findings of the study: the pursuit of new technological methods for presenting artworks results in the emergence of new aesthetic values; augmented reality art offers aesthetic, emotional, and cultural fulfillment to the audience—whether passive or interactive, Furthermore, the use of new technological tools, such as augmented reality, significantly reduces time, effort, and cost in developing innovative display methods, Lastly, the purpose of presenting artworks through interactive augmented reality is to educate the viewer about art, enhance their ability to appreciate the concept of the work, attract their attention, and ultimately nurture and elevate their aesthetic sensibility. Keywords: Aesthetics - Augmented Reality Technology - Display - Contemporary Artwork